2016
DOI: 10.5664/jcsm.6040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Mimics of Kleine-Levin Syndrome: A Survey in French-Speaking Switzerland

Abstract: Study Objective: Kleine-Levin syndrome (KLS) is a rare disease of unknown etiology, the diagnosis of which can be challenging. We aimed to estimate KLS prevalence in French-speaking Switzerland, and assess differences with mimicking conditions. Methods: In this cross-sectional study, KLS patients were identified through a population-based approach, including at our hospital and contacting all sleepcertified facilities and neurologists in French-speaking Switzerland. Furthermore, we identified patients referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although most cases of KLS are sporadic, familial occurrence (3 to 8% of relatives) has been reported in studies (5,9), and there are reports of concordant twin pairs (9, 10) which, considering the rarity of the condition (a few cases per million individuals) (11), suggests genetic or shared environmental effects. Early studies had suggested a human leukocyte antigen (HLA) association suggestive of an autoimmune mechanism (12), but this was not confirmed in larger samples (3,8,13).…”
mentioning
confidence: 99%
“…Although most cases of KLS are sporadic, familial occurrence (3 to 8% of relatives) has been reported in studies (5,9), and there are reports of concordant twin pairs (9, 10) which, considering the rarity of the condition (a few cases per million individuals) (11), suggests genetic or shared environmental effects. Early studies had suggested a human leukocyte antigen (HLA) association suggestive of an autoimmune mechanism (12), but this was not confirmed in larger samples (3,8,13).…”
mentioning
confidence: 99%
“…KLS is considered a markedly rare disease. Where examined, prevalence estimates range from 1.8 per million people in France [ 98 ] to 3.19 per million people in Switzerland [ 99 ]. It is not exclusive to a particular region, with documented cases throughout Europe, Asia, Africa and the Americas [ 100 , 101 ].…”
Section: Other Central Disorders Of Hypersomnolencementioning
confidence: 99%
“…Each analysis used the 1000 genomes European dataset matched by principle components as a control cohort. The burden analyses were focused only in rare variants (minor allele counts [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and restricted to predicted to be moderate or high modifiers as tagged by Annovar and SnpEff. Further, genes part of the rhythmic behavior pathway were collapsed, and SKAT based gene burden tests were performed (114) with resulting p-values adjusted using a 5% false discovery rate (FDR).…”
Section: Exome Sequencing Sample and Matched Controlsmentioning
confidence: 99%
“…Although most cases of KLS are sporadic, familial occurrence (3-8% of relatives) has been reported in studies (5, 9) and there are reports of concordant twin pairs (9, 10)which, considering the rarity of the condition (a few cases per million individuals) (11), suggests genetic or shared environmental effects. Early studies had suggested an HLA association suggestive of an autoimmune mechanism (12), but this was not confirmed in larger samples (3, 8, 13).…”
Section: Introductionmentioning
confidence: 99%